Intelligence, motivation and personality as predictors of training performance in the South African Army Armour Corps - Dijkman, Joy (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MComm (Industrial Psychology))--University of Stellenbosch, 2009.